Implementasi Penggunaan E Money Pada Ecommerce di Masa Pandemi Sebagai Pendukung Less Cash Society - Vania Sally Nabila; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
The development of information technology causes changes in all fields. One of them is the development of the payment system, where the payment system that was originally still in the form of cash has changed to non-cash. The use of non-cash or electronic money (e-money) has been widely used by the public in transactions, especially in transactions that are online or better known as electronic commerce (e-commerce). The use of e-money in e-commerce transactions can certainly support government programs in reducing the use of cash in transactions known as the Less Cash Society (LCS). This study uses descriptive qualitative methods, describing an event or events which are then described as they are without manipulation. Collecting data using library research, collecting references in the form of data in the form of narratives or sentences, documents, theories of opinion, pre-existing ideas which are then analyzed using data analysis techniques. The purpose of this study was to determine the effect of the level of use of e-money in e-commerce transactions during the pandemic on the LCS level.